Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3386/w17734
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change, Crop Yields, and Internal Migration in the United States

Abstract: We investigate the influence of weather anomalies on net migration in the Eastern United States using a county-level panel for the period from 1970 to 2009. One major mechanism is through the effect of weather on agricultural yields, which we examine in further detail using an instrumental variables approach. Our preferred model uses the seasonality of the sensitivity of corn yields to extreme heat over the growing season, which peaks during corn flowering, as instrument. The reduced-form estimate of the migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 27 publications
6
62
0
Order By: Relevance
“…The turning point value is at ∼2.2 m of average annual precipitation, which suggests that below the period-average annual precipitation of 2.2 m, any increase in rainfall reduces outmigration, but above it, any increase in rainfall increases outmigration such that with a rise in precipitation from 2.3 m to 3.3 m for example, a household's annual migration probability goes up by 0.00146. The effect, however, is much smaller compared with the effect of temperature on migration, which is consistent with previous findings that even agriculture-related outmigration is mostly sensitive to temperature rather than precipitation (15).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The turning point value is at ∼2.2 m of average annual precipitation, which suggests that below the period-average annual precipitation of 2.2 m, any increase in rainfall reduces outmigration, but above it, any increase in rainfall increases outmigration such that with a rise in precipitation from 2.3 m to 3.3 m for example, a household's annual migration probability goes up by 0.00146. The effect, however, is much smaller compared with the effect of temperature on migration, which is consistent with previous findings that even agriculture-related outmigration is mostly sensitive to temperature rather than precipitation (15).…”
Section: Resultssupporting
confidence: 92%
“…A rising temperature could therefore increase outmigration through a negative effect on income in agriculture as well as nonagricultural sectors and potentially over time by creating a less stable social environment. Prior work suggests there is evidence that temperature affects migration through its influence on agricultural productivity (13)(14)(15).…”
Section: Evidence For An Economic Mechanism By Which Environmental Famentioning
confidence: 99%
See 1 more Smart Citation
“…Boustan, Kahn and Rhode (2012) find similar outmigration in their study of the long-run impact of tornadoes in the United States during the 1920s and 1930s. Feng, Oppenheimer, and Schlenker (2012) document qualitatively similar patterns in a more recent period , suggesting that outmigration from areas experiencing negative agricultural productivity shocks still occurs today, particularly for young adults.…”
Section: Long-run Impacts Of Shockssupporting
confidence: 57%
“…Munshi (2003) showed that a decrease in rainfall in Mexico leads to more emigration to the US. Using country level panel data from 1970 to , Feng et al (2012 show a negative relationship between countries level outmigration and crop yields in the Corn-Belt in the US. More precisely, they find that a 1 % decline in crop yields due to weather shocks increase the migration of the adult population by 0.17%.…”
Section: Weather Shocks Agricultural Productivity and Migrationmentioning
confidence: 99%